(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Ruralmarketing facilitate flow of goods and service from rural producers to urbanconsumers at possible time with reasonable prices, and agricultureinputs/consumer goods from urban to rural. Marketing as a function has startedmuch earlier when civilization started but not recognized as marketing. Alleconomy goods are marketed in terms of goods and services (Barter system). Nowmoney is being practiced as a good exchanging medium. The market may be astreet, small town or metropolitan city. Developments in infrastructure,transport, and communication facilities have increased the scope of the ruralmarket. Indian rural marketing has always been complex to forecast and consistof special uniqueness. As two- thirds of the Indian population live in ruralareas, the market is vast than expected and so many companies are doing verygood business in the rural market of India. This paper discusses the present scenario of rural marketing inIndia and its importance, available opportunities, and also highlights theinfluencing factors and certain problems related to rural marketing. Further ithighlights the improvements that make the rural marketing system mosteffective.